Anxıolytıc, hypnotıc and antı-seızure actıvıtıes of Sonneratıa Apetala (Buch.-Ham.) fruıt through the GABAA ergıc and opıoıdergıc receptors - Badhon, Tazrın Kabır; Islam , M Rabıul; Hossaın, Sheıkh Julfıkar (Bangladesh Journal of Botany, 2025)
The study evaluated the extract of the fruits of Sonneratia apetala (Buch.-Ham.) for the treatment of anxiety, insomnia, and seizures. For this, the fruits were successively extracted with n-hexane (Hex), chloroform (Chl), and methanol (Met). All the extracts of the fruit showed an anxiolytic-like (p < 0.05 vs. control) effect in mice, as did diazepam (Dzp), with Hex showing the highest, followed by Met and Chl, in the elevated plus maze test. Flumazenil (Flu), a GABAA receptor antagonist, and naloxone (Nal), an opioid receptor antagonist, inhibited the anxiolytic effects of Hex and Met in mice. In the thiopental-induced mice model, Hex and Met extracts significantly shortened the latency time and extended the duration time of sleep compared to the control (C) mice. Moreover, Hex and Met extracts significantly delayed the appearance of the characteristic tonic-clonic seizures in the pentamethylenetetrazole-induced mice model. Therefore, S. apetala fruit possesses anxiolytic, hypnotic, and anti-seizure properties, which modulate the GABAA and opioid receptors. Bangladesh J. Bot. 54(4): 919-925, 2025 (December)